Login

 

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

 

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

Rješenje:

 

Rješenje:

 

rjskup-22-raz

 

Rješenje:

 rjskup-23-raz

 

    

Rješenje:

 

Rješenje:

 

Rješenje:

Rješenje:

 

 

Rješenje:

a)f:A→B   f(x) = x + 3   A={2,3,4,6}

 

   f(2) = 2 + 3 = 5

   f(3) = 3 + 3 = 6

   f(4) = 4 + 3 = 7

   f(6) = 6 + 3 = 9

 

x

2

3

4

6

f(x)=x+3

5

6

7

9

 

 

 

b)f:A→B     f(x)=3x-2     A={2,3,4,6}

 

   f(2) = 3·2 – 2 = 6 – 2 = 4

   f(3) = 3·3 - 2 = 9 - 2 = 7

   f(4) = 3·4 – 2 = 12 – 2 = 10

   f(6) = 3·6 - 2 = 18 - 2 = 16

 

x

2

3

4

6

f(x)=x+3

4

7

10

16

 

 

 

b)f:A→B     f(x)=2x+1     A={2,3,4,6}

   f(2) = 2·2 + 1 = 4 + 1 = 5

   f(3) = 2·3 + 1 = 6 + 1 = 7

   f(4) = 2·4 + 1 = 8 + 1 = 9

   f(6) = 2·6 + 1 = 12 + 1 = 13

 

x

2

3

4

6

f(x)=x+3

5

7

9

13

 

 

 

Rješenje:

 Rješenje:

Rješenje:

 

Rješenje: